Regularities of Youngster Free Time Physical Activity in a Latvian Secondary School (Baltic Journal of Sport and Health Sciences, 2017)
Background. Article investigates youngster physical activity (PA) habits, finding tendencies of PA participation, factors promoting and impeding it.Methods.  The  methods  include  literature  analysis,  cross-sectional  study  with  self-reported  questionnaire consisting of 11 questions and statements about most popular leisure sports, frequency, venues, significant others, and  neighbourhood  influence. The  questionnaire,  based  on  EU  Special  Eurobarometer  412  “Sport  and  Physical Activity”, research in Northern and Eastern countries, as well as in the Netherlands, was sent by e-mail to 91 Grade 10 subjects in a Latvian mainstream secondary school in the academic year of 2015/2016; the response rate was 60%. The statistical analysis was carried out with Index method and SPSS software.Results. The Cronbach’s alpha for neighbourhood section (5 items) of the questionnaire was .74. The validity of the questionnaire was based on the consideration that the questions were drawn from surveys, described in reliable sources. Most of the students with friends or alone did three sports at sport schools (69.50%), as well as in parks, woods, seaside, at home, most popular sports were team games (basketball, volleyball), winter sports (skiing and snowboarding), fitness sports (running), strength sports (gym workout) and gymnastics. Statistically significant, medium  strong  correlations  were  found  between  good  relations  with  neighbours  and  high  level  of  well-being  (r = .38, p = .05). Conclusion.  The student choice to practice team games and gymnastics might be influenced by traditional youngster values and their status as trendy sports, but winter sports in Latvia traditionally are among the most popular ones. Good neighbourhood relations could help youngsters be more physically active.Keywords:  mainstream school students, leisure sports, neighbourhood social capital.